Governança corporativa, a implantação e a criação de valor em empresas familiares: um estudo de caso múltiplo no Estado do Rio Grande do Sul - Cofferi, Luis Eduardo (Universidade do Vale do Rio dos Sinos, 2021)
This work aims to research and study the implementation of corporate governance and the adoption of corporate governance practices in family businesses in the north of Rio Grande do Sul, at a time of technological, political, demographic and economic changes. In this challenging and transformative landscape, the next generations of family business leaders face greater challenges – and opportunities – than their parents and grandparents could ever have imagined. Considering that the significant majority of companies are family businesses in the universe of companies from Rio Grande do Sul and Brazil, the study of the theme Corporate Governance, the implementation and creation of value in family businesses has a significant potential impact on the quality of management of this universe of companies. The methodology chosen was the multiple case study, as this made it possible to study different realities of family businesses in Rio Grande do Sul. Each case is presented and analyzed, but highlighting the differences and similarities that generate learning on the subject. Questionnaires were applied, internal documents were analyzed and in-depth interviews were conducted with owners, family members and managers. The results obtained showed which corporate governance practices were implemented in the four companies studied and the impacts of their non-implementation.
Keywords: Empresa familiar; Governança corporativa; Teoria da agência; Family business; Corporate governance; Agency theory; ACCNPQ::Ciências Sociais Aplicadas::Administração